The sequel - Korelitz, Jean Hanff, 1961- (Celadon Books, 2024)
"Anna Williams-Bonner has taken care of business. That is to say, she's taken care of her husband, bestselling novelist Jacob Finch Bonner, and solved the mystery of the anonymous plagiarism accusations that tormented him. Now she is living her life, content to enjoy her husband's royalty checks in perpetuity, but literary celebrity continues to beckon, and this time the book in question is her own debut novel, The Afterword. After all, how hard can it really be to write and publish a universally lauded best seller? Then, in the wake of The Afterword's great success, Anna begins to receive anonymous accusations of her very own. Surely there is no one out there who still knows the truth about her colorful life, so who is sending her these excerpts of a justly lost manuscript by a justly unpublished author? Who knows her true name and origins? Who understands the exact nature of her many, many transgressions? Anna has come too far, and worked too hard, to lose this life. She cannot rest until she has eradicated the threat and reclaimed, definitively and permanently, her sole and uncontested right to her own story"--